2015
DOI: 10.1371/journal.pone.0123888
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ultrasound Guided Implantation of VX2 for Creation of a Rabbit Hepatic Tumor Model

Abstract: Creation of a VX2 tumor model has traditionally required a laparotomy and surgical implantation of tumor fragments. Open surgical procedures are invasive and require long procedure times and recovery that can result in post-operative morbidity and mortality. The purpose of this study is to report the results of a percutaneous ultrasound guided method for creation of a VX2 model in rabbit livers. A total of 27 New Zealand white rabbits underwent a percutaneous ultrasound guided approach, where a VX2 tumor fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Two rabbits had no tumors seen on follow-up imaging. Therefore, tumor development was seen in 24/26 (92%) rabbits 25 . During the follow-up period, tract seeding was seen in 8% of rabbits and 38% had extra-hepatic metastatic disease 26 - 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Two rabbits had no tumors seen on follow-up imaging. Therefore, tumor development was seen in 24/26 (92%) rabbits 25 . During the follow-up period, tract seeding was seen in 8% of rabbits and 38% had extra-hepatic metastatic disease 26 - 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that animals in group A, in which tumor fragments were implanted by the conventional method, experienced an increased incidence of peritoneal nodules (36.8%) compared with group B. Peritoneal nodules may be attributed to the high invasive and metastatic properties of VX2 carcinoma (12,13). Previous studies have demonstrated that the majority of rabbits underwent metastasis ~40 days after tumor implantation (8,14).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are many models of orthotopic hepatocellular carcinoma in a rat model, including the Morris (McA-RH7777), [ 24 ] Novikoff (N1S1),[ 24 , 25 ] and AS30D [ 26 ] and VX2 in the rabbit model. [ 27 ] However, as interventional oncologists expand their practice to treat liver dominant hepatic metastases, little is known about treatment efficacy. Translational models of metastatic disease allow for better understanding of safety and efficacy of the different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%